ExplanationThe factored form of the Difference of Squares (one of the “special products” you need to memorize for the exam) is comprised of the terms given in this problem:

\(x^2 - y^2 = (x + y)(x - y)\)

Substitute the values \(\sqrt{12}\) and \(\sqrt{3}\) in place of (x – y) and (x + y), respectively:

x^2 - y^2 = \(\sqrt{12} \times \sqrt{3}\)

Combine 12 and 3 under the same root sign and solve:

\(x^2 - y^2 =\sqrt{12} \times \sqrt{3}\)

\(x^2 - y^2 =\sqrt{36}\)

\(x^2 - y^2 = 6\)

_________________

Sandy

If you found this post useful, please let me know by pressing the Kudos Button

Try our free Online GRE Test